The effect of storage temperatures and polyethylene packaging on the keeping quality of apple fruits cv. Rome Beauty grown under environmental condition of El-Gabel El-Khder area - Gadalla, Suleiman O (Al-Mukhtar Journal of Sciences, 2004)
This study was conducted during the seasons of 2000 and 2001 on apple fruits (Malus domestica) cv. Rome beauty grown under environmental condition of eastern part of Libya, at El-Gable El- Akhder (the green mountain) area to investigate, the effect of storage temperatures; 0 , 3 and 5° C, and the effect of packing in polyethylene bags at 5° C, on the keeping quality of the fruits during their storage for 4 months. Also one of the aim of this study to evaluated the possibility of using packing in polyethylene bags at 5° C, as alternator of storing fruits at lower temperature (0 and 3° C ) . By following up the changes in the chemical and physical parameters such as acidity % (Mallic acid), Total soluble solid (%TSS), firmness (kg/cm2), weight loss % and wastage % (due to physiological disorders and pathogens infection), after 4 months storage, the results indicated that the fruits stored at 0 and 3° C had better quality (significantly had greater retention of acidity, firmness and had lower percentage of weight loss and wastage) than those stored at 5° C. Also the fruits stored at 0° C showed significantly lower percentage of weight loss and wastage only than those stored at 3° C. On the other hand the fruits packed in polyethylene bags (perforated or non perforated) stored at 5° C , showed higher wastage % (mainly due to internal breakdown) as comparing with those non packed in polyethylene bags (mainly due to pathogen infection). While the fruits packed in polyethylene bags (perforated or non perforated) stored at 5°C, had significantly greater retention of TSS % than those (non packed in polyethylene bags) stored at the same temperature. Moreover the results indicated that the fruits packed in non perforated polyethylene bags had significantly less weight loss percentage among all the fruits of the other treatments except those (non packed in polyethylene bags) stored at 0° C, where the value of the weight loss was the same.